Effect of levothyroxine therapy on hypothyroid symptoms and tiredness among adults having subclinical hypothyroidism - Kumar, Mishra Rajiv (Journal of Neonatal Surgery, 2025)
For adults with subclinical hypothyroidism(SCH), levothyroxine is ineffective. Treatment may aid those with more symptoms. For older people with SCH and more symptoms, levothyroxine may alleviate hypothyroid symptoms and fatigue. The study included 63 subjects aged 65 and older who had chronic subclinical hypothyroidism (SCH), which is defined as having a thyrotropin level between 4.6 and 19.9 mIU/L after more than 3 months, along with normal free thyroxine levels. Patients from the Autonomous State Medical College in Kushinagar, Uttar Pradesh, participated in the OPD study. One-year Thyroid-Related Quality-of-Life survey change High-symptom load (baseline scores >30 or >40) vs. low-symptom burden hypothyroid symptom and tiredness scores (range 0-100, higher scores signal greater symptoms). 13 had hypothyroid symptoms >30 and 13 were fatigued >40. The Hypothyroid Symptoms score improved similarly for levothyroxine (mean within-group change -12.3) and placebo (10.4) in the high symptom group at 6 months. These findings older people with SCH and significant baseline symptom burden did not benefit from levothyroxine or fatigue compared to placebo